Partial Root Zone Drying Irrigation Improves Water Use Efficiency but Compromise the Yield and Quality of Cotton Crop. Issue 13 (20th July 2021) - Iqbal, Rashid; Raza, Muhammad Aown Sammar; Rashid, Muhammad Adil; Toleikiene, Monika; Ayaz, Muhammad; Mustafa, Farhan; Ahmed, Muhammad Zeshan; Hyder, Sajjad; Rahman, Muhammad Habib-Ur; Ahmad, Salman; Aslam, Muhammad Usman; Haider, Imran
ABSTRACT: Water shortage is the main limitation for agricultural production in many parts of the world. Drought or unavailability of water may seriously limit plant growth as well as yield. A pot experiment was carried out to evaluate the effects of various irrigation strategies, i.e., Full (FI), deficit (DI) and partial root-zone drying (PRD) on physiological, biochemical and yield-related attributes of cotton crop. Irrigation treatments started 60 days after planting and lasted for 60 days. For FI and DI, 100% and 50% of evapotranspiration (ET) was replaced by irrigating the entire pot surface every 4–5 days. For PRD, root system was split into two equal halves and during each irrigation event, only one-half of the root system was irrigated with the same amount of water as applied to DI, and subsequently, irrigation was switched to the second half.PRD irrigation significantly improved WUE, which was 21% and 26% higher than FI and DI, respectively. Higher ABA production under PRD reduced stomatal conductance and net photosynthesis. The activity of antioxidant enzymes namely superoxide dismutase, peroxidase, catalase and ascorbate peroxidase was significantly higher under PRD than DI and FI. Magnitude of osmotic adjustment (i.e. total sugar and proline content) was lowest and highest under FI and PRD, respectively. However, PRD reduced chlorophyll content index, seed cotton yield and fiber quality (fiber strength, fiber length, fiber fineness) as compared to FI. The results indicated that despite improving the WUE, PRD tended to compromise the yield and quality of cotton crop. Results imply that PRD treatment can be an option under water shortage; however, its suitability and efficacy should further be tested under field conditions by applying irrigation water in alternate rows.